Bioprinting of gelatin-based materials for orthopedic application - Waidi, Yusuf Olatunji; Kariim, Ishaq; Datta, Sudipto (Frontiers in Bioengineering and Biotechnology, 2024)
Bio-printed hydrogels have evolved as one of the best regenerative medicine and tissue engineering platforms due to their outstanding cell-friendly microenvironment. A correct hydrogel ink formulation is critical for creating desired scaffolds that have better fidelity after printing. Gelatin and its derivatives have sparked intense interest in various biomedical sectors because of their biocompatibility, biodegradability, ease of functionalization, and rapid gelling tendency. As a result, this report emphasizes the relevance of gelatin-based hydrogel in fabricating bio-printed scaffolds for orthopedic applications. Starting with what hydrogels and bio-printing are all about. We further summarized the different gelatin-based bio-printing techniques explored for orthopedic applications, including a few recent studies. We also discussed the suitability of gelatin as a biopolymer for both 3D and 4D printing materials. As extrusion is one of the most widely used techniques for bio-printing gelatin-based, we summarize the rheological features of gelatin-based bio-ink. Lastly, we also elaborate on the recent bioprinted gelatin-based studies for orthopedics applications, the potential clinical translation issues, and research possibilities.